Energizing teacher education and professional development with problem-based learning - Levin, Barbara B. (Association for Supervision and Curriculum Development, 2001)
How can we help both beginning and experienced teachers engage students in today's diverse classrooms? How can we focus on actual problems that teachers face? This book offers a learning tool-problem-based learning (PBL). PBL is an instructional method that encourages learners to use critical thinking and problem solving as they apply content knowledge to real-world problems and issues. Editor Barbara Levin and the book's contributing authors believe that if teachers are to use PBL effectively with their K-12 students, they need to personally experience PBL themselves. Levin provides field-tested examples of how teacher educators have used PBL in many professional development settings. Based on actual PBL units and activities contributed by various authors, the book describes how teachers tackled authentic problems that required them to find, evaluate, and use resources to learn, just as they expect their students to do when using PBL. A brief introduction explains why and how to use PBL with teachers. Chapters 1-5 focus on how the chapter authors used PBL in different teacher preparation courses at several universities. Chapters 6 and 7 show how the authors, working with experienced teachers, used PBL in inservice and staff development settings. The final chapter offers answers to frequently asked questions about using PBL with teachers.